2011
DOI: 10.1134/s1068162011040157
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase-induced biodegradation of single-walled carbon nanotubes is mediated by hypochlorite

Abstract: Broad prospects for the use of single-walled carbon nanotubes (SWNTs) in medicine and biotechnology raise the concerns about both their toxicity, and the mechanisms of biodegradation and excretion from the body. SWNTs biodegradation as a result of catalytic activity of myeloperoxidase (MPO) was shown in the isolated MPO system as well as in the suspension of neutrophils [Kagan V.E., et al., 2010]. In the present study we analyzed the ability of different MPO-produced oxidants to participate in the modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 29 publications
1
62
0
1
Order By: Relevance
“…Previous studies have demonstrated the effect of ClO − on carbon nanotubes. [27][28][29][30] The authors utilised the action of myeloperoxidase to convert H 2 O 2 to ClO − , which subsequently acted to oxidise the carbon nanotubes and ultimately degrade them. The oxidative action of ClO − was confirmed, as aqueous NaClO was used as a positive control to degrade the CNMs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the effect of ClO − on carbon nanotubes. [27][28][29][30] The authors utilised the action of myeloperoxidase to convert H 2 O 2 to ClO − , which subsequently acted to oxidise the carbon nanotubes and ultimately degrade them. The oxidative action of ClO − was confirmed, as aqueous NaClO was used as a positive control to degrade the CNMs.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, they demonstrated how functionalized SWCNTs carrying defect sites on the sidewall and tips of the carbon nanotubes could be degraded by plant-derived horse radish peroxidase (HRP) [34]. CNTs are found to be biodegradable also by means of other kind of peroxidases [35,36,37], by bacteria [38] or by other biological mechanisms [39,40]. …”
Section: What Are Cnts and Why Are They Relevant For Sensingmentioning
confidence: 99%
“…Other carbon-based nanoparticles have been shown to undergo similar MPO-catalyzed modifications and degradation (16, 127). It has been proposed that hypochlorite and MPO reactive intermediates are possible pathways in which the oxidative biodegradation process occurs (15, 16, 127, 128). Certainly the biodegradation of SWCNTs has tremendous implications for biopersistence and potential long-term health effects from prolonged exposures.…”
Section: Engineered Nanomaterialsmentioning
confidence: 99%